2017
DOI: 10.1007/s13593-017-0459-1
|View full text |Cite
|
Sign up to set email alerts
|

Proper selection of substrates and crops enhances the sustainability of Paris rooftop garden

Abstract: Rooftop gardens are a promising way to supplement the growing demand for local food production, and are especially relevant in large cities with acute space constraints. However, they face the challenge of achieving viable food productivity while minimizing their impacts on the environment, two priorities that often oppose one another. Also, the actual impacts of management practices, which are deemed environmentally friendly in principle, are rarely quantified. Therefore, evaluations that encompass all compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Finally, the economic dimension of UFP has rarely been evaluated in the literature. Sanyé-Mengual et al [16,17] and Dorr et al [31] combined LCA with life cycle costing (LCC) to integrate the environmental and economic dimensions of sustainability for case studies of rooftop agriculture. The economic profitability of emerging types of UFP have also been evaluated for vertical farming [32].…”
Section: Quantifying the Sustainability Of Ufpmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the economic dimension of UFP has rarely been evaluated in the literature. Sanyé-Mengual et al [16,17] and Dorr et al [31] combined LCA with life cycle costing (LCC) to integrate the environmental and economic dimensions of sustainability for case studies of rooftop agriculture. The economic profitability of emerging types of UFP have also been evaluated for vertical farming [32].…”
Section: Quantifying the Sustainability Of Ufpmentioning
confidence: 99%
“…Studies in warm climate areas highlighted the efficiency of UFP cases and the potential environmental benefits from minimizing the distance between producers and consumers (i.e., reduced transport, packaging and food losses) [16,17,21,45,50]. On the contrary, studies in mild climate cities found that the UFP typology and the productivity of the system would determine whether UFP has environmental benefits compared to conventional food systems [18,31]. Finally, Forchino et al [44] and Maucieri et al [22] investigated the environmental impacts of aquaponics, where the production of fish and vegetables are integrated, paying attention to different production techniques [44] as well as the potential use of aquaponics as an educational tool [22].…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations